2001
DOI: 10.1046/j.1365-2680.2001.00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoid release and constrictor responses to noradrenaline in the rat mesenteric vascular bed in non‐insulin‐dependent diabetes mellitus

Abstract: 1. The administration of streptozotocin (STZ) to 2-day old rats induced a non-insulin-dependent diabetes mellitus (NIDDM)-like state, with mild hyperglycaemia and no alterations in body weight at the adult age. 2. In the isolated and perfused mesenteric vascular bed of NIDDM animals, the constrictor responses to either noradrenaline (NA) or potassium chloride (KCl) were not modified as compared with age-matched non-diabetic controls. 3. The reduction in NA contractions induced by the cyclooxygenase inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
3
6
0
Order By: Relevance
“…The increased a-adrenergic responsiveness of diabetic vas deferens observed in this study, may be attributable to new receptor synthesis or activation of post-receptor events due to diabetesinduced neuropathy rather than an enhancement in a-adrenoceptor affinity, as the pD 2 for the contractile effects of noradrenaline was found to be unchanged. This is in agreement with the results of other groups [5,7,19]. The increased contractile responses of vas deferens from diabetic rats to phenylephrine, and the decreased responses to nerve stimulation in diabetic rats, has been explained with denervation-like supersensitivity in receptor-mediated processes [6].…”
Section: Discussionsupporting
confidence: 92%
“…The increased a-adrenergic responsiveness of diabetic vas deferens observed in this study, may be attributable to new receptor synthesis or activation of post-receptor events due to diabetesinduced neuropathy rather than an enhancement in a-adrenoceptor affinity, as the pD 2 for the contractile effects of noradrenaline was found to be unchanged. This is in agreement with the results of other groups [5,7,19]. The increased contractile responses of vas deferens from diabetic rats to phenylephrine, and the decreased responses to nerve stimulation in diabetic rats, has been explained with denervation-like supersensitivity in receptor-mediated processes [6].…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that, in the presence of indomethacin, the synergistic interaction between locally produced vasoconstrictor prostanoids and phenylephrine may be blocked, resulting in a consequent reduction of the effects of phenylephrine. Moreover, the effects of indomethacin on the vascular responsiveness to phenylephrine were observed both in preparations with and without endothelium, supporting previous studies that demonstrated a synergistic participation of non-endothelial vasoconstrictor prostanoids in the contractile actions of norepinephrine in rat mesenteric arteries (Peredo, 2001;Peredo, 2003) and aorta (Lamb et al, 1994) and of phenylephrine in rat aorta (Connoly et al, 1998).…”
Section: Discussionsupporting
confidence: 87%
“…This fact suggests that phenylephrine may stimulate the production of vasoconstrictive prostanoids by smooth muscle in the MVB. Similar results were obtained by Manku and Horrobin, 1976, Peredo and Adler-Graschinsky, 2000, and Peredo, 2001. These investigators demonstrated that indomethacin reduced the vasoconstrictive effect of noradrenaline in the mesenteric arterial bed of rats and suggested that the constrictive effect of noradrenaline involves the participation of two different pathways of arachidonic acid metabolism, i.e., the cyclooxygenase pathway and the lipoxygenase pathway.…”
Section: Discussionsupporting
confidence: 74%
“…These data show that in diabetic animals phenylephrine is unable to release vasoconstrictive prostanoids from MVB smooth muscle and that this is the major mechanism explaining the difference in reactivity to this agent observed in diabetic rats. Using noradrenaline with an agonist, Peredo et al, 1999, Peredo, 2001 obtained similar data for rats with diabetes mellitus in two distinct models (STZ diabetic rats and rats with diabetes similar to the human type II). However, 8 weeks after STZ induction of diabetes, the vasoconstrictive effect of noradrenaline was again reduced by indomethacin perfusion.…”
Section: Discussionmentioning
confidence: 85%